Implikasi Ketegangan Lintas Batas Iran-Pakistan bagi Keamanan Regional Asia Selatan 2021-2024 - Ganjar Widhiyoga; Cindy Alvian Ika Dewani (Journal of Social Contemplativa, 2026)
This article analyses the implications of Iran-Pakistan cross-border tensions for South Asian regional security between 2021 and 2024. It focuses on the links between Balochistan border insecurity, sectarian rivalry, competing economic corridors, and weak regional cooperation mechanisms. The study uses qualitative document analysis of official statements, scholarly works, books, policy reports, and credible news sources. Its analytical framework combines the security dilemma and regional security complex theory. The article argues that Iran-Pakistan tensions are not merely a bilateral issue but part of an interdependent regional security pattern. The reciprocal strikes in January 2024 reveal the centrality of sovereignty and retaliation, while the subsequent de-escalation indicates that both states still have incentives to contain the crisis. The main implications for South Asia are heightened security dilemmas and vulnerable border governance; human security and economic connectivity face potential risks. The article contributes by distinguishing non-state armed incidents from an interstate crisis and observed consequences from risks that remain potential.